2022
DOI: 10.3390/ma15124163
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Tensile Behavior of Selected Tire Cords Using Novel Testing Equipment

Abstract: Aramid and polyamide cords are used in a wide range of applications, particularly in the automotive industry (tire reinforcement) and textile industry for military and fireguard purposes. The problem of the reliable experimental study of tensile behavior of synthetic cords is considered in this paper. In the available standards for synthetic cord testing, particularly ASTM D 885-03, the tensile test must result with the cord damage in the middle of gauge length, and the cords should be fixed in the machine cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Tests on nylon/PET hybrid cords [3] and on aramid/nylon hybrid cords [4] have been also carried out and discussed. Experimental studies on the tensile behavior of aramid and polyamide cords are reported in [5]. Cyclic tests on nylon66 cords are described in detail in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tests on nylon/PET hybrid cords [3] and on aramid/nylon hybrid cords [4] have been also carried out and discussed. Experimental studies on the tensile behavior of aramid and polyamide cords are reported in [5]. Cyclic tests on nylon66 cords are described in detail in [6].…”
Section: Introductionmentioning
confidence: 99%